Antifungal Susceptibly Testing by Concentration Gradient Strip Etest Method for Fungal Isolates: A Review - Eric Dannaoui; Ana Espinel-Ingroff (Journal of Fungi, 2019)
: Antifungal susceptibility testing is an important tool for managing patients with invasive fungal infections, as well as for epidemiological surveillance of emerging resistance. For routine testing in clinical microbiology laboratories, ready-to-use commercial methods are more practical than homemade reference techniques. Among commercially available methods, the concentration gradient Etest strip technique is widely used. It combines an agar-based diffusion method with a dilution method that determinates a minimal inhibitory concentration (MIC) in µg/mL. Many studies have evaluated the agreement between the gradient strip method and the reference methods for both yeasts and filamentous fungi. This agreement has been variable depending on the antifungal, the species, and the incubation time. It has also been shown that the gradient strip method could be a valuable alternative for detection of emerging resistance (non-wild-type isolates) as Etest epidemiological cutoff values have been recently defined for several drug-species combinations. Furthermore, the Etest could be useful for direct antifungal susceptibility testing on blood samples and basic research studies (e.g., the evaluation of the in vitro activity of antifungal combinations). This review summarizes the available data on the performance and potential use of the gradient strip method.